INFLUENCE OF EXCIPIENTS ON THE PROCESS OF MIXING WITH THYME ESSENTIAL OIL IN THE PRODUCTION OF A POWDER MASS BASED ON IT - Зарівна, Надія; Горлачук, Наталія (SWorldJournal, 2023)
The paper presents the effect of excipients on the process of mixing with thyme essential oil in obtaining a powder mass based on it. Having analyzed the saturation of the pharmaceutical market of drugs with mucolytic activity, it was pointed out the feas